7th Five Year Plan 1988-93 and Perspective Plan 1988-2003 - Planning Commission (Planning Commission, 1988)
The Highlights of the Draft Seventh Plan were released by the Planning Commission on March 9, 1988. This document constitutes the detailed proposals of the Planning Commission for the Seventh Five Year Plan. The Chapters included are in a preliminary draft form and will undergo revisions in the light of discussions with the Federal Ministries, Provincial Governments and professional and trade bodies.
Government of Pakistan Planning Commission
Government of Pakistan Planning Commission